Perbedaan Hasil Urinalisis Leukosit pada Penderita Diabetes Melitus Tipe 2 Berdasarkan Lama Waktu Menderita di Puskesmas Muara Dua Kota Lhokseumawe - Nur Usradti, Ayundira (Pustaka Galeri Mandiri, 2025)
Leukocyturia is a serious problem in the context of health, especially for individuals with low immune systems. Leukocyturia can occur in patients with Type 2 diabetes mellitus (Type 2 DM) due to high and uncontrolled glucose levels for a long time, causing a decrease in phagocytosis function by leukocyte cells. This makes Type 2 DM patients susceptible to infection and inflammation of the bladder. The purpose of this study was to determine the differences in leukocyte urinalysis results in patients with Type 2 DM based on the duration of suffered at the Muara Dua Health Center in Lhokseumawe City. This research is a quantitative study that uses a cross sectional study design and non probability sampling technique with accidental sampling type. Patient characteristics were obtained by interview. The research material was urine taken from 99 respondents. The examination was carried out by dipstick method and the statistical analysis was carried out by Kruskal Wallis test. The results showed that most patients with type 2 diabetes mellitus were aged 56-65 years, female, had a duration of Type 2 DM for 1-5 years. A total of 17 respondents (89.5%) experienced leukocyturia in the large category. Leukocyturia in the large category is more likely to occur in patients aged 56-65 years, female, having a duration of Type 2 DM between 11-15 years. The test results showed a p value = 0.000 (?0.1) which means there is a significant difference in the results of leukocyte urinalysis in patients with Type 2 DM based on the duration of suffered at the Muara Dua Health Center in Lhokseumawe City. Follow-up of this study is very important to identify and manage the risk of urinary tract infection (UTI) more effectively